Environmental assessment for bisphenol-a and polycarbonate - Chow, Jimmy T. (Kansas State University, 2007)
Polycarbonate products have been used extensively world wide for decades because they are lightweight, shatter-resistant and considered to be safe. Polycarbonate is a thermoplastic that is used to make compact discs, phones, lenses, and food contact products such as water bottles, baby bottles and food storage containers. For more than half century, there has been interest in polycarbonate (PC) products and the monomer bisphenol-A (BPA) because BPA can leach from food polycarbonate containers. The environmental fate for both chemicals in air, water and soil is of interest, also. To understand the fate of polycarbonate, its main degradation pathways, main degradation mechanisms and main products are reviewed. These pathways are thermal degradation, photo-degradation and hydrolysis under different conditions. Furthermore, key topics like PC degradation kinetics and PC chemical resistance are part of this comprehensive discussion. The biodegradation of BPA has been thoroughly studied. About twelve lab methods for environmental fate are summarized and reviewed to understand the “big picture” for BPA degradation. This includes screening tests, which assess the ready and inherent degradability, to simulation tests for surface waters, soils and wastewater treatment systems. The testing of all methods is examined under conditions close to the real environment fate. Furthermore, the fate distribution for BPA based on the Equilibrium Criterion Model (EQC) model is reviewed. Extensive research on polycarbonate and BPA has been conducted in the last fifty years. During this time, both chemicals have been studied and tested by industry and government agencies. The pharmacological test results from major studies indicate that consumer exposure to BPA at concentrations normally experienced in daily living does not pose a risk to human health. On the other hand, minor toxicological studies indicate potential risks to human health. Research on health and safety are continuing.
Keywords: Environmental fate; Polycarbonate; BPA; Biodegradation; Chemical resistance; toxicology; Engineering, Chemical (0542); Engineering, Environmental (0775); Health Sciences, Toxicology (0383)